The Effect of Tax Revenue Sharing Funds in Encouraging Fiscal Independence and Local Own-Source Revenue Growth - Saruni; Harin Tiawon; Alexandra Hukom (Institut Bisnis dan Informatika Kesatuan, 2025)
Effective regional fiscal management is crucial for sustainable development, yet many regions rely heavily on central transfers, limiting their financial autonomy. This study investigates the role of the tax revenue sharing fund in enhancing fiscal independence and promoting the growth of regional own-source revenue. The study aims to analyze both the direct effect of the fund on regional own-source revenue and its indirect effect through fiscal independence. A quantitative approach using path analysis with panel data was employed, and classical assumption tests confirmed no violations in normality, multicollinearity, heteroscedasticity, autocorrelation, or linearity. The model explains 59% of the variance in regional own-source revenue growth. Findings show that the tax revenue sharing fund significantly influences fiscal independence and directly affects regional own-source revenue growth. Fiscal independence also mediates the relationship between the fund and revenue growth, with a total effect of 0.646. The study concludes that the fund plays a strategic role as both a fiscal transfer and a catalyst for strengthening local revenue structures, supporting sustainable regional autonomy.